Use of Individual Learning Model Class Meetings in Improving Student Learning Outcomes in Religious Subjects - Niva, Matteson; Maharjan, Kailie; Maq, Mumu Muzayyin; Mark, Eladdadi; Sulaeman, Otong (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
Religious studies are one of the most important lessons in the world of education, but student learning outcomes are still low. One way to improve student learning outcomes is to use available learning models. One of the learning models that can be used is the individual learning model. This research aims to determine student learning outcomes in religious subjects using an individual learning model. This research uses quantitative methods with a survey model using Google Form and in-depth interviews using the WhatsApp application. The objects of this research are students studying religious subjects and teachers of religious subjects. The results of this research show that individual learning using the class meeting model is very effective in improving student learning outcomes in religious subjects. For this reason, this learning model can be used by teachers in carrying out the teaching and learning process. The limitation of this research is that the researcher did not include a learning design that can be used by students and teachers to further maximize individual learning using the class meeting model, so the researcher hopes that future researchers will create a learning design that can make it easier for related parties to maximize individual learning by class meeting model.